On Pointwise ?-Statistical Convergence of Order ? of Sequences of Fuzzy Mappings - Et, Mikail (Univ Nis, Fac Sci Math, 2014)
In this study, we introduce the concepts of pointwise lambda-statistical convergence of order alpha of sequences of fuzzy mappings and strongly pointwise (V, lambda, p)-summable of order alpha of sequences of fuzzy mappings. Some relations between pointwise lambda-statistical convergence of order alpha and strongly pointwise (V, lambda, p)-summable of order alpha of sequences of fuzzy mappings are given.
Keywords: Generalized Difference-Sequences; Approximation; Spaces